The INFLUENCE OF PRICE AND SERVICE QUALITY ON CUSTOMER LOYALTY OF INTERNET SERVICE PROVIDERS IN KOTA JAMBI - Gufron; Johannes, Johannes; Fazri, Andang (Journal of Business Studies and Management Review, 2025)
This study aims to analyze the influence of price and service quality on customer loyalty toward internet service providers in Jambi City, with digital dependency as a moderating variable. The rising penetration of internet usage has intensified competition among service providers, making pricing strategies and service quality critical factors in retaining customers. A quantitative approach was employed through a survey of 384 customers, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that both price and service quality have a positive and significant effect on customer loyalty, with service quality exerting a stronger influence than price. Digital dependency significantly moderates the relationship between price and customer loyalty, weakening its impact, whereas in the relationship between service quality and customer loyalty, it significantly strengthens the effect. These findings indicate that among customers with high levels of digital dependency, service quality becomes a more dominant factor than price. The implications of this study emphasize the need for internet service providers to combine competitive pricing strategies with continuous improvement in service quality, while also considering customers’ levels of digital dependency when designing effective retention strategies.